Determinants that affect generation Z consumer loyalty in Wardah skincare - Zhulkarnain, Nur Azhizhah; Nurhalim, Asep; Mahanani, Yekti; Hassan, Rusni (IPB University, 2024)
In 2022, the skincare market in Indonesia was observed to generate revenue of approximately US 2.05 billion. In this market, consumers tend to prefer local products that adhere to the standards of halal and are widely recognized. A prominent, current, and popular skincare brand that has been found to adhere to these standards is Wardah. Between 2020 and 2021, Wardah experienced an increase in market share, showing a growing preference for its products among consumers. However, from 2023 to 2024, a significant decline has been observed in the market share of the brand, signaling a reduction in consumer preference. This trend is a critical concern for the company, as it emphasizes the need to address the factors contributing to the decline and to implement strategies that are capable of enhancing the appeal of products produced by Wardah, enabling the brand to remain competitive. Therefore, this study aimed to analyze the factors influencing the loyalty of Generation Z consumers toward Wardah skincare products in the Jabodetabek region. The demographic was observed because, conventionally, Generation Z, which constitutes around 27% of the population of Indonesia (75 million people), is often targeted as the primary market to build consumer loyalty for the majority of products. In order to achieve the study objectives, a sample of 135 respondents was selected using a non-probability sampling method, specifically the purposive sampling technique. The data was then analyzed using the Structural Equation Model-Partial Least Square (SEM-PLS) method. The obtained results showed that brand trust and perceived value had a significant and positive impact on consumer loyalty. These observations suggest that companies should focus on maintaining and strengthening brand trust, fostering a strong brand community, and raising awareness about the importance of halal certification in skincare products. Additionally, efforts should be made to educate consumers about the value of halal-certified skincare products, as this can further enhance brand loyalty.